Mursia spiridonovi, new name for Mursia minuta Spiridonov & Apel, 2007 preoccupied by Mursia minuta Karasawa, 1993 (Decapoda: Brachyura: Calappidae) - Karasawa, Hiroaki (Zootaxa, 2018)
The name Mursia minuta Spiridonov & Apel, 2007, was given to a living species from the Indian Ocean (Spiridonov & Apel 2007: 2870, figs. 2G, H, 4E, F, 8C, 10A–D, 11A, B, 12A, B). This name is preoccupied by the senior primary homonym Mursia minuta Karasawa, 1993, for a Pliocene fossil species from Japan (Karasawa 1993: 45, pl. 8, figs. 8, 10, 13, 14). In accordance with Article 60 of the International Code of Zoological Nomenclature (ICZN 1999: 62, 63) a new replacement name, Mursia spiridonovi is here proposed for Mursia minuta Spiridonov & Apel, 2007. It is named for V. A. Spiridonov (Institute of Oceanology of the Russian Academy of Sciences, Moscow), in honor of his pioneering work on the extant decapods.